Subregional Density of Neurons, Neurofibrillary Tangles and Amyloid Plaques in the Hippocampus of Patients With Alzheimer’s Disease - Furcila, Diana; Domínguez-Álvaro, Marta; DeFelipe, Javier; Alonso-Nanclares, Lidia (Frontiers in Neuroanatomy, 2019)
A variety of anatomical alterations have been reported in the hippocampal formation of patients with Alzheimer’s Disease (AD) and these alterations have been correlated with cognitive symptoms in the early stages of the disease. Major hallmarks in AD are the presence of paired helical filaments of tau protein (PHFTau) within neurons, also known as neurofibrillary tangles (NFTs), and aggregates of amyloid-β protein (Aβ) which form plaques in the extracellular space. Nevertheless, how the density of plaques and NFTs relate to the severity of cell loss and cognitive decline is not yet clear. The aim of the present study was to further examine the possible relationship of both Aβ plaques and NFTs with neuronal loss in several hippocampal fields (DG, CA3, CA1, and subiculum) of 11 demented AD patients. For this purpose, using stereological techniques, we compared neuronal densities (Nissl-stained, and immunoreactive neurons for NeuN) with: (i) numbers of neurons immunostained for two isoforms of PHFTau (PHFTau-AT8 and PHFTau-pS396); and (ii) number of Aβ plaques. We found that CA1 showed the highest number of NFTs and Aβ plaques, whereas DG and CA3 displayed the lowest number of these markers. Furthermore, AD patients showed a variable neuronal loss in CA1 due to tangle-related cell death, which seems to correlate with the presence of extracellular tangles.